Urban systems and urban development in the People's Republic of China - Zhao Chen; Ming Lu (Asian Development Bank Institute (ADBI), 2015)
The People's Republic of China (PRC) is experiencing a trend toward population concentration in its large coastal cities. However, at the same time, there is also a distortion of city size toward small cities in the country. That is to say, the urban population in the PRC should further concentrate in large cities rather than be more equally spread out. Cross-country analysis indicates that the population size of the primary city in the PRC is smaller than its predicted value. This paper suggests that the PRC government should adjust its policies on future urbanization for fewer restrictions on the further growth of megacities.
Keywords: O18; P25; R12; 330; urbanization; megacities; population concentration